Cashlees Schools: Smart Solution or New Burden - Rosidah, Rosidah; Vidiati, Cory (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research aims to analyze the Cashless Payment System where cashless payments are available, what are the benefits, challenges and obstacles, the impact it has, implementation and case studies, as well as Recommendations and Best Practices. This research uses the Libery reasech research method or literature study. The results of this research are that cashless payments make transactions very easy, there are many challenges in making these payments, the implementation in the case study is also very effective, especially for Jakarta residents, the impact can also be good or bad in educational and social sectors, and there are many recommendations for maximizing cashless payments in order to maximize online payments.